(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Congenital heart disease (CHD) is one of the frequent congenital health issues in neonates. Early diagnosis is a key factor to combat this problem. This study aims to assess the frequency and common types of CHD among neonates presenting to a tertiary care hospital, Karachi. Patients and methods: This descriptive cross-sectional study was conducted in a Neonatal Intensive Care Unit (NICU) of National Institute of Child Health (NICH), Karachi from March to September 2017. All neonates of gestational age ≥37 weeks with suspected CHD (presence of blue-tinged skin, i.e. cyanosis on routine clinical examination) were included. Information regarding presence of CHD and its types were collected along with the demographic characteristics and history of the patients. Results: Of 134, frequency of CHD was observed in 126 (94%) patients. Out of these 126 CHD patients, Ventricular septal defect (VSD) was observed in 49 (38.9%), patent ductal arteriosus (PDA) in 29 (23%), atrial septal defect (ASD) was observed in 19 (15.1%), Transposition of great arteries (TGA) in 18 (14.3%), and tetralogy of Fallot (TOF) in 14 (11.1%) patients. A significant association of VSD was observed with neonatal age (p = <0.001), ASD with neonatal age (p = 0.037) and maternal age (p = 0.025), while TGA was found significantly associated with neonatal age (p<0.001). Conclusion: CHD was observed in majority of the suspected patients with VSD as commonest type of congenital heart diseases among neonates.